Intravenous thrombolysis prior to mechanical thrombectomy does not affect clinical or procedural outcomes in patients with large vessel occlusion acute ischemic stroke. (June 2022) - Platko, Steven; Bensabeur, Fatima; Rotsching, Nicholas; Wagner, Jacob; Markert, Ronald J.; Terry, John B.; Cheng-Ching, Esteban
Highlights: Intravenous thrombolysis before thrombectomy is not associated with improved outcomes. Intravenous thrombolysis does not have an impact on the technical aspects of thrombectomy. Bleeding risk is not increased with intravenous thrombolysis prior to thrombectomy. Administration of intravenous thrombolytics is not associated with delays in thrombectomy. Abstract: Mechanical thrombectomy (MT) has revolutionized the care of large vessel occlusion acute ischemic strokes (LVOAIS). However, the benefit of intravenous thrombolysis prior to MT remains unproven. Two recent trials showed equivocal results regarding the benefits of pre-MT intravenous thrombolysis in predominantly Asian populations. We evaluated clinical outcomes and procedural metrics for patients with LVOAIS who were treated with MT alone compared to those who were treated with both intravenous tPA and MT. In a retrospective study, LVOAIS patients treated with MT, with or without preceding intravenous thrombolysis, between January of 2017 and December of 2019 were identified. Patients were treated according to contemporary guidelines. Baseline demographic and clinical characteristics, procedural metrics, and clinical outcomes were collected. Among LVOAIS patients, those treated with intravenous thrombolysis and MT did not differ from those with MT alone on clinical outcomes at three months. Further, the two groups did not differ on thrombectomy procedure times, recanalization rates, and symptomatic intracranial hemorrhage rates. In our patients with LVOAIS, intravenous thrombolysis combined with MT offered no advantage compared to MT alone in clinical outcomes or recanalization rates. Our results are consistent with earlier studies in other populations. In addition, our results suggest that IV tPA does not impact the ease of clot removal by MT. Further studies will evaluate how newly available thrombolytic agents may benefit patients eligible for MT.